Less is more; intermediate oiling has a greater impact than heavy oiling on feather permeability in Northern Gannets (Morus bassanus) - Nina Rogerson; Mark Jessopp; Emma Murphy (Marine Biology, 2025)
Northern gannets are the largest migratory seabird in the Northern Atlantic and are vulnerable to oil pollution as a result of industrialisation spreading to marine environments. This study experimentally investigated the effect of crude oil on gannet feathers under laboratory conditions, with respect to (a) mass accumulation from contact with oil on water surface, and (b) water permeability of feathers following oiling. Gannet feather mass increased by as much as 945% following heavy oil contact, with even light oiling increasing feather mass by 93.4% on average. Intermediate oiling corresponding to thin sheens on the water surface had the most damaging effect on feather permeability, letting water through feathers almost twice as quickly as controls, while thick crude oil slicks had the opposite effect, slowing water permeability 1.48 times compared to controls. Drastically lower water permeability in gannet feathers, compared to previously published data from Manx shearwaters, was explained by a denser arrangement of feather barbs and barbules in gannets, effectively demonstrating how seabirds differ in their vulnerability to oiling. This study suggests that a species’ susceptibility to the impacts of oil pollution is strongly related to its feather structure, which is linked to individual foraging strategies, with potential consequences for survival and breeding success affecting populations.